APPLICATION OF THE CSI METHOD TO TEST CONSUMER SATISFACTION: A CASE STUDY OF PETROL STATIONS - Agnieszka DUDZIAK; Monika STOMA; Grzegorz ZAJĄC (Scientific Journal of Silesian University of Technology. Series Transport)
Conducting research on the quality of service and customer satisfaction is currently necessary for the proper and effective functioning of any organization. One of the organizations that have changed in recent years is petrol stations. In this paper, the Customer Satisfaction Index (CSI) is used to measure the quality of services and customer satisfaction. This research was carried out with the use of a proprietary questionnaire in which the respondents assessed the level of service at petrol stations. The obtained results allowed identifying the most important areas for the customers of petrol stations. In addition, the developed quality map indicated areas that should be given special attention, improved and those that are least important to customers. The conducted analyzes indicate that the CSI method used in this study is a tool that enables the assessment of customer satisfaction in a complex organization such as a petrol station.